1996
DOI: 10.1111/j.1365-2885.1996.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of doxycycline in turkeys

Abstract: The pharmacokinetic parameters of doxycycline (DOX) were determined in 3 day, 3-, 6- and 12-week-old fasted turkeys, after a single intravenous (i.v.) dose of 25 mg doxycycline. HCl/kg body weight. Doxycycline disposition fitted an open two-compartment model. The mean (+/-SD) elimination half-life was 10.6 +/- 0.7, 10.8 +/- 1.5, 7.9 +/- 1.4 and 10.0 +/- 0.9 h in 3 day, 3-, 6- and 12-week-old turkeys, respectively. Mean (+/- SD) total body clearance was 0.19 (+/-0.01), 0.27 (+/-0.03), 0.11 (+/-0.03) and 0.06 (+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 4 publications
6
34
1
2
Order By: Relevance
“…The discrepancies between values calculated for pharmacokinetic parameters may be attributed to the animal species, the drug formulation employed, the age, size or sex of the animals, to differences in fatty tissue deposits between animal species or breeds, or even to inter-individual variations (Riond et al, 1989;Jha et al, 1989). Doxycycline pharmacokinetics after PO administration were best described in this animal species by a 2-compartment open model, which is in accordance with previous studies in pigs (Baert et al, 2000), calves with immature ruminal function (van Gool et al, 1986;Meijer et al, 1993), chickens (Anadó n et al, 1994;Espigol et al, 1997;Laczay et al, 2001) and turkeys (Santos et al, 1996).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The discrepancies between values calculated for pharmacokinetic parameters may be attributed to the animal species, the drug formulation employed, the age, size or sex of the animals, to differences in fatty tissue deposits between animal species or breeds, or even to inter-individual variations (Riond et al, 1989;Jha et al, 1989). Doxycycline pharmacokinetics after PO administration were best described in this animal species by a 2-compartment open model, which is in accordance with previous studies in pigs (Baert et al, 2000), calves with immature ruminal function (van Gool et al, 1986;Meijer et al, 1993), chickens (Anadó n et al, 1994;Espigol et al, 1997;Laczay et al, 2001) and turkeys (Santos et al, 1996).…”
Section: Discussionsupporting
confidence: 84%
“…As expected in ruminants, the results of our study indicate that doxycycline is partially absorbed when administered orally. Meijer et al (1993) reported higher bioavailability values in calves with immature ruminal function (69 ± 12%), but most previous studies observed an absorption value similar to ours, including studies performed in chickens (41.3 ± 2%) (Anadó n et al, 1994), turkeys (25-64%) (Santos et al, 1996), and pigs (21.2 ± 7.5%) (Baert et al, 2000). Although the loss of doxycycline in the forestomachs may play an important role, these discrepancies are in accordance with those reported for other tetracyclines, and are related to the animal species studied (Nielsen and GyrdHansen, 1996), the pharmacokinetic curve-fitting routines or the analytical techniques used (Meijer et al, 1993), the drug formulation administered, and the health status of the animals (Abd El-Aty et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations